Primeval very low-mass stars and brown dwarfs: III. The halo transitional brown dwarfs - Zhang, Zeng Hua; Homeier, Derek (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. We report the discovery of an esdL3 subdwarf, ULAS J020858.62+020657.0, and a usdL4.5 subdwarf, ULAS J230711.01+014447.1. They were identified as L s
Gesehen am 30.01.2019